Improved Work Function of Poly(3,4-ethylenedioxythiophene): Poly(styrenesulfonic acid) and its Effect on Hybrid Silicon/Organic Heterojunction Solar Cells - Shen, Xiaojuan (Nanoscale Res Lett, 2016)
Hybrid silicon/organic solar cells have been recently extensively investigated due to their simple structure and low-cost fabrication process. However, the efficiency of the solar cells is greatly limited by the barrier height as well as the carrier recombination at the silicon/organic interface. In this work, hydrochloroplatinic acid (H(2)PtCl(6)) is employed into the poly(3,4-ethlenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) solution, and the work function (WF) of the PEDOT:PSS layer has been successfully improved. Based on the Pt-modified PEDOT:PSS layer, the efficiency of the silicon/PEDOT:PSS cell can be increased to 11.46%, corresponding to ~20% enhancement to the one without platinum (Pt) modification. Theoretical and experimental results show that, when increasing the WF of the PEDO:PSS layer, the barrier height between the silicon/PEDOT:PSS interface can be effectively enhanced. Meanwhile, the carrier recombination at the interface is significantly reduced. These results can contribute to better understanding of the interfacial mechanism of silicon/PEDOT:PSS interface, and further improving the device performance of silicon/organic solar cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1759-0) contains supplementary material, which is available to authorized users.